Apostasy as a Factor Causing the Dissolution of Marriage in the Compilation of Islamic Law: An Analysis from the Perspectives of Classical and Modern Texts - Riadatul Muhimmah; Abdul Rozak; Izzul Mutho (al-Afkar, Journal For Islamic Studies, 2026)
In classical literature studies, when one spouse apostatizes, two types of rulings are made. The first ruling states that their marriage is immediately annulled, which is generally found in the books of the Hanafi and Maliki schools. The second ruling demands that the couple divorce, which is more commonly found in the books of the Shafi‘i and Hambali schools. Although these two opinions appear different, the general consensus in classical literature is that the marriage is considered dissolved (furqah). Modern legal texts tend to agree with the contents of these classical texts. In the Compilation of Islamic Law, there are two articles that regulate apostasy in the context of marriage, namely Article 75 and Article 116. Article 75 implicitly indicates that the act of apostasy results in the annulment of the marriage, but Article 70 does not mention apostasy as a reason for the annulment of marriage. Meanwhile, Article 116 does not list apostasy as a reason for divorce, except when there is discord within the household. This seems contradictory, considering the Explanation of the Compilation of Islamic Law mentions that the material on marriage law is sourced from 38 fiqh books, including 13 books from the Shafi‘i school. This research is a normative legal study with a conceptual approach. Based on the research conducted, the author concludes that Article 75, which implicitly states that apostasy causes the annulment of marriage, aligns with some classical and modern fiqh texts. However, Article 116, which regulates reasons for divorce, does not align with classical and modern fiqh texts, as in these books, apostasy as a reason for divorce does not require discord within the household.